A Quasi-Experimental Study to Assess Effectiveness of Drumstick Leaves Powder Consumption among Selected Hypertensive Patients in Selected Rural Area of Maharashtra - Dilip Bandbe, Shrushti (Indian Journal of Nursing Sciences, 2024)
Background: This study was a quasi-experimental study to assess effectiveness of drumstick leaves powder consumption among selected hypertensive patients in selected rural area of Maharashtra. Objective: The objective of the study is to determine whether drumstick leaf powder consumption affects blood pressure (BP) levels among hypertensive patient and to find an association between post-test BP levels and selected demographic factors of hypertension patients. Methods: The study design is quasi-experimental two group pre-test and post-test. Sixty hypertensive patients were chosen using nonprobability purposive sampling. Results: The unpaired t-test was used for assessing the effectiveness and comparing the means of different days. The comparison between post-test level of systolic BP among selected hypertensive patients in experimental group and control group, the mean and standard deviation is 17.96 ± 3.75. The unpaired t-test value is 19.85, df=58, P < 0.05, S(t-table value=2 for df = 58) also comparison between post-test level of diastolic BP among selected hypertensive patients in experimental group and control group, the mean and standard deviation is −11.07 ± 0.55. The unpaired t-test value is 11.91, df=58, P < 0.05, S (t-table value=2 for df = 58); hence, calculated values are greater than table value, which shows significant difference in pre-test and post-test values. Conclusion: The analysis indicates that using drumstick leaf powder to lower BP in hypertensive patients is an effective intervention. Furthermore, it was noted that except age, habit of cigarette smoking, and habit of alcohol consumption have significant association with effectiveness of drumstick leaves powder among selected hypertensive patient.